Exchange Rates and Capital Flows - Brooks, Robin; Edison, Hali.; Kumar, Manmohan; Sloek, Torsten (Washington, D.C. : International Monetary Fund, 2001)
This paper explores the ability of portfolio and foreign direct investment flows to track movements in the euro and the yen against the dollar. Net portfolio flows from the euro area into U.S. stocks-possibly reflecting differences in expected productivity growth-track movements in the euro against the dollar closely. Net FDI flows, which capture the recent burst in cross-border M and A activity, appear less important in tracking movements in the euro-dollar rate, possibly because many M and A transactions consist of share swaps. Movements in the yen versus the dollar remain more closely tied to such conventional variables as the current account and interest differential.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet